Social Antiaddictive Advertising as Speech Genre: Communicative Strategies and Tactics (Proceedings of Southern Federal University. Philology, 2019)
Lyudmila A. Brusenskaya (Rostov-on-Don, Russian Federation)Antiaddictive social advertising is a special speech genre of modern communication with specific features determined by the target setting and the chosen strategy. Advertising can be considered as a special functional style, within which separate genres are distinguished, first of all commercial advertising and social advertising.   Social advertising, which refers to ethical categories, has become especially popular because society is faced with such problems, the solution of which depends on mass behavior. Advertising has become an integral part of the daily life of a person. Since advertising is mass-replicated in the media, it can enter the consciousness of the addressee, even against his/her will and desire, no wonder advertising is sometimes defined as the “fifth power” after media, whose power is considered the “fourth power”. Therefore, it is so important for advertising to follow the moral principles of society, it is so important to comply with modern ethical and linguistic norms. If commercial advertising is widespread, the antiaddictive one is little known. Many specialists in advertising argue for the need of the strategy of “shock” advertising, a remarkable feature of which is hyperbolization, used to cause fear. In antiaddictive advertising there is often a morphological imperative in the meaning of categorical motivation. It is justified as such advertizing has to be as much as possible appellate, has to be understood unambiguously. Anti-drug social advertising should show positive, motivation to a healthy lifestyle.Key words: social advertising, prevention of addictions, speech genre, perlocutivity, ethical and linguistic norms.DOI 10.23683/1995-0640-2019-3-105-113